If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) = 2(3x + -4) Reorder the terms: 3(5 + 2x) = 2(3x + -4) (5 * 3 + 2x * 3) = 2(3x + -4) (15 + 6x) = 2(3x + -4) Reorder the terms: 15 + 6x = 2(-4 + 3x) 15 + 6x = (-4 * 2 + 3x * 2) 15 + 6x = (-8 + 6x) Add '-6x' to each side of the equation. 15 + 6x + -6x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + 0 = -8 + 6x + -6x 15 = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 15 = -8 + 0 15 = -8 Solving 15 = -8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1d/4=-2/4 | | -7+5y=-16 | | 3(3x-6)-18=-3(5x+5)-4 | | -9=-3y-7x | | -8x-y=-6 | | 0.3x+3.8=x | | 33.8-32= | | -9x+3y=9 | | -7x+5=-16 | | 1/9c+36=7/9c+5 | | -2+x/3=5 | | -30=5a | | 6(7b-7)=-4+4b | | y=0.8x+3 | | 2/3(12-3h)=h | | 7d+4d-6d+2-8=2d | | 3y=-4x+12 | | -7(1+2x)=23-8x | | -3(3x-6)-18=-3(5s+5)-4 | | -4(1+7m)=30+6m | | n=250/100(2) | | 4(k-9)+18=6 | | -8a^2-6a+9=0 | | -y+2=0 | | 4n+4/2=-13 | | y=0.9x+3 | | 1.92+.04x=1.92+.08x | | 2x+6/x+3 | | 25X+6-27X=5-9 | | 3(z-2)=2(z+7) | | -7(3n+2)=-8n+38 | | 7+36=-11 |